PELATIHAN DAN PENDAMPINGAN TATA CARA PENYELENGGARAAN JENAZAH - HAWA, HAWA; Faridah, Faridah (LP2M Universitas Islam Ahmad Dahlan, 2024)
Caring for and organizing bodies for Muslims is fardhu kifayah. If there is someone or several groups of people who have carried out the obligation, then the obligation of others to carry it out has fallen. There are four obligations of Muslims after the death of a person, namely bathing, shrouding, praying and burying. Organizing the bodies was carried out at the Nurul Hayat Mosque in Safaere Hamlet, Puncak Village, South Sinjai District, this activity was carried out in order to improve the skills of the community in taking care of the corpse properly and correctly in accordance with the teachings of Islamic law, so that one day they are needed to be ready.